By no means there yet: centring the voices of Black, Indigenous, and youth of colour climate activists in Ontario - Grewal, Rupinder Kaur (My University, 2024)
This critical qualitative inquiry delves into the experiences of Black, Indigenous, and youth of colour activists involved in the climate justice movement. Semi-structured narrative interviews were conducted with 15 Black, Indigenous and youth in Ontario, aged 18 to 29, engaged with a climate justice organization for a minimum of six months. Utilizing timeline mapping and semistructured interviews, participants highlighted pivotal life events shaping their justice-oriented values. Two overarching themes emerged: 1) Deliberately Unheard? Conveying the Challenges Encountered by BIPoC Youth Climate Activists, and 2) Empowering Echoes: Nurturing Identity, Shaping Communities, and Forging New Pathways for BIPoC Youth Leaders. Early connections to the land, familial influences, and the Land Back movement significantly informed participants' activism, emphasizing the need for intersectional environmentalism. Amidst experiences of racism within the movement and the predominant whiteness of youth protests, BIPoC youth navigate a diverse range of climate emotions and advocate for leadership opportunities and dedicated spaces for youth to foster intergenerational knowledge transfer. The study calls for systemic change and concludes with recommendations to enhance climate justice education in schools, offering insights to inspire future generations for a more equitable and sustainable future, especially for the most vulnerable of peoples.
Keywords: Youth climate justice movement; BIPoC youth activists; Climate justice education; Intersectional environmentalism